Dental students' preferences regarding teaching methods in Riyadh - Huda I Tulbah; Eman M Alhamdan; Amal S Alqahtani; Ghaida A Alduhayan; Lamees S Albedaiwi (Wolters Kluwer Medknow Publications, 2019)
Objectives: The objectives of this study are to identify and compare the preferences of male and female undergraduate dental students on different aspects of teaching lectures and clinical courses in two major dental schools in Riyadh: the College of Dentistry of King Saud University (KSU) and Riyadh Elm University (REU). Materials and Methods: A questionnaire of three parts was formulated: Part 1 contained demographic data; Part 2 covered information about: the length and timing of lectures, schedule announcement, attendance, having materials before sessions, interactive sessions, and getting handouts and clinical demonstrations; and Part 3 covered preferences regarding logbooks, written assignments, quizzes, resources, team-based learning (TBL), and student feedback. The questionnaire was distributed to male and female undergraduate dental students in two dental schools in Riyadh. A stratified random sampling method was applied to collect a sample of 345 participants. Results: Among the participants, 159 were from KSU and 186 were from REU and 183 were male and 162 were female. About 74% of the dental students preferred the use of logbooks, and 40% preferred not to have written assignments. A total of 63% preferred using several resources, and REU students (72%) stated this preference more. More than half of the students (58%) agreed on having frequent quizzes. More REU (61%) than KSU students (38%) preferred (TBL). The majority (78%) preferred to take their feedback into consideration. Conclusions: This study illustrated that logbooks, writing assignment, and quizzes are learning styles that are still acceptable by dental students. Teachers should consider the feedback from the students when evaluating course outlines.